Fibrinogen Mitigates Prion-Mediated Platelet Activation and Neuronal Cell Toxicity - Gautam, Deepa; Kailashiya, Jyotsna; Tiwari, Arundhati; Chaurasia, Rameshwar Nath; Annarapu, Gowtham K.; Guchhait, Prasenjit; Dash, Debabrata (Frontiers in Cell and Developmental Biology, 2022)
Prion peptide (PrP) misfolds to infectious scrapie isoform, the β pleat-rich insoluble fibrils responsible for neurodegeneration and fatal conformational diseases in human. The amino acid sequence 106–126 from prion proteins, PrP(106–126), is highly amyloidogenic and implicated in prion-induced pathologies. Here we report a novel interaction between PrP(106–126) and the thrombogenic plasma protein fibrinogen that can lead to mitigation of prion-mediated pro-thrombotic responses in human platelets as well as significant decline in neuronal toxicity. Thus, prior exposure to fibrinogen restrained PrP-induced rise in cytosolic calcium, calpain activation and shedding of extracellular vesicles in platelets while it, too, averted cytotoxicity of neuronal cells triggered by prion peptide. Interestingly, PrP was found to accelerate fibrin-rich clot formation, which was resistant to plasmin-mediated fibrinolysis, consistent with enhanced thrombus stability provoked by PrP. We propose that PrP-fibrinogen interaction can be clinically exploited further for prevention and management of infectious prion related disorders. Small-molecules or peptides mimicking PrP-binding sites on fibrinogen can potentially mitigate PrP-induced cellular toxicity while also preventing the negative impact of PrP on fibrin clot formation and lysis.